A COMPARATIVE STUDY OF GRADES 6 TO 9 STUDENTS’ ATTITUDES TOWARD THAI LANGUAGE ACQUISITION CLASS AND THAI LANGUAGE LITERATURE CLASS AT A TRILINGUAL SCHOOL IN THAILAND - Jirananda, Tatchanan; González, Orlando (Journal of Educational Review Faculty of Education in MCU, 2023)
This study aimed to determine whether there was a significant difference, within and among grades, in Grades 6 to 9 students’ attitudes toward Thai Language Acquisition and Thai Language Literature classes at a trilingual school in Thailand. A conveniently chosen sample of 239 students, enrolled in the target school during the academic year 2021-2022, participated in this study. For the data collection, the Attitudes Toward Thai Language Acquisition Class Questionnaire, and the Attitudes Toward Thai Language and Literature Class Questionnaire, adopted from two subscales from Gardner’s (2010) Attitude/Motivation Test Battery (AMTB), were used. From performing the descriptive statistics on the collected data, it was found that the levels of attitudes toward Thai Language Acquisition class for Grades 6 and 7 students were partially positive, and partially negative for Grades 8 and 9 students. Moreover, it was found that the levels of attitudes toward Thai Language Literature class for Grades 6 and 7 students were positive, and partially positive for Grades 8 and 9 students. From conducting a statistical comparative analysis, it was found a significant difference between participants’ attitudes toward Thai Language Acquisition class and Thai Language Literature class for Grade 7 and Grade 8 students, with the mean scores difference favoring the latter class numerically. Moreover, the attitudes toward Thai Language Acquisition class were significantly more positive in Grade 6 students than in Grade 7, and Grade 8 at a trilingual school in Thailand, while the attitudes toward Thai Language Literature class were found to be significantly more positive in Grades 6 and 7 students than in Grade 9 students. Based on the research findings, recommendations for students, teachers, administrators, and future researchers are provided.